Ethnomedicine and neuropsychopharmacology in Mesoamerica. (5th October 2021) - Geck, Matthias S.; Lecca, Daniele; Marchese, Giorgio; Casu, Laura; Leonti, Marco
Abstract: Ethnopharmacological relevance: The burden of disease caused by mental and neurological disorders is increasing globally, to a disproportionate degree in Latin America. In contrast to the many psychoactive plants with a use history in Mesoamerican cultures, the translation to the wider population of knowledge around numerous botanicals used contemporarily by indigenous Mesoamerican societies to treat psychological and neurological disorders did not receive the same attention. Material and methods: We used the previously published Mesoamerican Medicinal Plant Database to extract species and associated botanical drugs used as treatments for illnesses associated with the nervous system by Mesoamerican cultures in Belize, Guatemala, and Mexico. With the critical use of published pharmacological literature, the cross-culturally most salient genera are systematically reviewed. Results: From 2188 plant taxa contained in the database 1324 are used as treatments for illnesses associated with the nervous system. The ethnomedical data was critically confronted with the available biomedical literature for the 58 cross-culturally most salient genera. For a considerable proportion of the frequently used taxa, preclinical data are available, mostly validating ethnomedicinal uses. Conclusion: This quantitative approach facilitates the prioritization of taxa for future pre-clinical, clinical and treatment outcome studies and gives patients, practitioners, and legislators a fundamental framework of evidence, on which to base decisions regarding phytomedicines. Graphical abstract: Image 1